2023
DOI: 10.1002/aenm.202300152
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Carbon Coating and Defect Engineering Promote RuO2 as an Efficient Catalyst for Acidic Oxygen Evolution Reaction with Super‐High Durability

Abstract: Developing acid‐stable electrocatalysts with high activity for the oxygen evolution reaction (OER) is of paramount importance for many energy‐related technologies. This work reports that ultrathin nitrogen‐doped carbon coated oxygen‐vacancy (Vo·) rich RuO2 nanoparticles on carbon nanotubes (CNTs) (NC@Vo·‐RuO2/CNTs‐350), synthesized through the controlled calcination in air, is an efficient acid‐stable electrocatalyst for the OER. It only needs an overpotential of 170.0 mV to drive 10.0 mA cm−2 and shows excell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…3a shows that the OER catalysed by the V-Ru x Mn 1− x O 2 NWs has an onset potential of 1.37 V ( E on ) and they only need an overpotential of ∼200.0 mV to drive a current density of 10 mA cm −2 ( η 10 ). The OER activity of the V-Ru x Mn 1− x O 2 NWs is much higher than those of com-RuO 2 ( E on = 1.44 V and η 10 = 302.0 mV, close to the reported values 10,24 ) and commercial IrO 2 (com-IrO 2 , E on = 1.47 V and η 10 = 330 mV, close to the reported values 25,26 ). In particular, the η 10 value of V-Ru x Mn 1− x O 2 NWs is lower than that of other acidic OER catalysts reported recently, such as Ni–RuO 2 (214.0 mV) 18 and Si-RuO x @C (220.0 mV) 24 (Table S1†).…”
supporting
confidence: 81%
See 1 more Smart Citation
“…3a shows that the OER catalysed by the V-Ru x Mn 1− x O 2 NWs has an onset potential of 1.37 V ( E on ) and they only need an overpotential of ∼200.0 mV to drive a current density of 10 mA cm −2 ( η 10 ). The OER activity of the V-Ru x Mn 1− x O 2 NWs is much higher than those of com-RuO 2 ( E on = 1.44 V and η 10 = 302.0 mV, close to the reported values 10,24 ) and commercial IrO 2 (com-IrO 2 , E on = 1.47 V and η 10 = 330 mV, close to the reported values 25,26 ). In particular, the η 10 value of V-Ru x Mn 1− x O 2 NWs is lower than that of other acidic OER catalysts reported recently, such as Ni–RuO 2 (214.0 mV) 18 and Si-RuO x @C (220.0 mV) 24 (Table S1†).…”
supporting
confidence: 81%
“…3 Tremendous work has demonstrated that the electronic structure of the active sites is the major factor determining the activity of the catalysts, since it governs the adsorption of reactants, the transformation of intermediates, and the desorption of products. 10 Generally, the methods used for the modulation of the electronic structure of the active sites include metal doping, 11 vacancy generation, 12 active facet control, 13 heterostructuring, 7 etc. As reported previously, metal doping can optimize the electronic structure of the active sites at the catalyst surface through charge redistribution, which lowers the energy barrier of the rate-determining step (RDS) for the OER.…”
mentioning
confidence: 99%
“…37 However, the O1 peak associated with metal oxides and the O3 peak belonging to lattice-defective oxygen on the metal surface are all absent, which can illustrate there are no platinum oxides existing in Pt-NPs-bonded@CNT. 38 This result demonstrates that divalent platinum is formed by the formation of chemical bonds between platinum and carbon (Pt−C) in carbon nanotubes. The metallic state of platinum is related to the platinum nanoparticles bonded in carbon nanotubes.…”
Section: Resultsmentioning
confidence: 91%
“…In this approach, the passivating material should be stable under the PEMWE operating conditions of harsh acidic electrolytes and a strong oxidative potential range. Viable passivation materials include TiO 2 , carbon, and other metal species. For example, Tran-Phu et al prepared Co 3 O 4 catalysts passivated with a TiO 2 layer and investigated the impact of the TiO 2 layer thickness on the OER stability. When the thickness of the TiO 2 layer was 4.4 nm, the catalyst achieved the maximum stability, as identified by the potential retention time of 75 h at the current density of 10 mA ( t 10 ).…”
Section: Design Strategies For Improving Catalytic Performancementioning
confidence: 99%